การแจ้งข่าวร้ายในการดูแลแบบประคับประคอง:การทบทวนหลักฐานเชิงประจักษ์ - กัญญาวีร์ สิริโรจนามณี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Breaking bad news is the most important step in palliative care because an appropriate approach leads to positive consequences for patients, family, and health care providers. This integrative review aimed to explore the method of breaking bad news and its impact in palliative care. Evidence published in Thai and English from 2002 to 2013 was reviewed using a systematic review guideline, developed by the Joanna Briggs Institute (2008). The study instruments consisted of 1) the Research Screening Form, 2) the Critical Appraisal Form, and 3) the Data Extraction Form. Data were analyzed using descriptive statistics to describe characteristic of research and content analysis. The search strategy found 6 studies meeting the inclusion criteria. There were 3 qualitative studies, 2 descriptive studies, and 1 experimental study. The results revealed that: 1. Method of breaking bad news: The results did not find an empirical method for breaking bad news but can provide guidelines as follows: physicians should be the persons who break bad news, most immediately after patients are diagnosed with terminal illness. Physicians need to have communication skills to do this. Before breaking bad news, physicians should; build on their relationship with patients and families, use a sitting position during breaking bad news, and inform truth diagnosed information. The physician should, explain about the prognosis of disease, treatment plan, and side effects of treatment. This information should be provided step-by-step for meeting patients’ needs, using adequate time and appropriate language, showing empathy, giving hope and encouragement, while giving opportunities for accepting selected treatment plan of patients and families. They must also show respect for patients’ decisions. In addition, physicians should provide information about end of life care to patients and families. 2. Impact of breaking bad news: patients and families receive knowledge and understanding about the illness, treatment plan and side effects of treatment. They have opportunities to select a treatment plan, have options regarding quality of life, have opportunities to prepare for the end of their lives, and patients should also have satisfaction with information received from physicians. The results of this integrative review provided background information to understand the issues of, and how to break bad news. The replication studies regarding breaking bad news in palliative care, especially experimental studies should be conducted.